Combined effects of diethylpropion and alcohol on locomotor activity of mice: Participation of the dopaminergic and opioid systems - Gevaerd M.S.* (1999)
The widespread consumption of anorectics and combined anorectic + alcohol misuse are problems in Brazil. In order to better understand the interactive effects of ethanol (EtOH) and diethylpropion (DEP) we examined the locomotion-activating effects of these drugs given alone or in combination in mice. We also determined whether this response was affected by dopamine (DA) or opioid receptor antagonists. A total of 160 male Swiss mice weighing approximately 30 g were divided into groups of 8 animals per group. The animals were treated daily for 7 consecutive days with combined EtOH + DEP (1.2 g/kg and 5.0 mg/kg, ip), EtOH (1.2 g/kg, ip), DEP (5.0 mg/kg, ip) or the control solution coadministered with the DA antagonist haloperidol (HAL, 0.075 mg/kg, ip), the opioid antagonist naloxone (NAL, 1.0 mg/kg, ip), or vehicle. On days 1, 7 and 10 after the injections, mice were assessed in activity cages at different times (15, 30, 45 and 60 min) for 5 min. The acute combination of EtOH plus DEP induced a significantly higher increase in locomotor activity (day 1: 369.5 ± 34.41) when compared to either drug alone (day 1: EtOH = 232.5 ± 23.79 and DEP = 276.0 ± 12.85) and to control solution (day 1: 153.12 ± 7.64). However, the repeated administration of EtOH (day 7: 314.63 ± 26.79 and day 10: 257.62 ± 29.91) or DEP (day 7: 309.5 ± 31.65 and day 10: 321.12 ± 39.24) alone or in combination (day 7: 459.75 ± 41.28 and day 10: 427.87 ± 33.0) failed to induce a progressive increase in the locomotor response. These data demonstrate greater locomotion-activating effects of the EtOH + DEP combination, probably involving DA and/or opioid receptor stimulation, since the daily pretreatment with HAL (day 1: EtOH + DEP = 395.62 ± 11.92 and EtOH + DEP + HAL = 371.5 ± 6.76; day 7: EtOH + DEP = 502.5 ± 42.27 and EtOH + DEP + HAL = 281.12 ± 16.08; day 10: EtOH + DEP = 445.75 ± 16.64 and EtOH + DEP + HAL = 376.75 ± 16.4) and NAL (day 1: EtOH + DEP = 553.62 ± 38.15 and EtOH + DEP + NAL = 445.12 ± 55.67; day 7: EtOH + DEP = 617.5 ± 38.89 and EtOH + DEP + NAL = 418.25 ± 61.18; day 10: EtOH + DEP = 541.37 ± 32.86 and EtOH + DEP + NAL = 427.12 ± 51.6) reduced the locomotor response induced by combined administration of EtOH + DEP. These findings also suggest that a major determinant of combined anorectic-alcohol misuse may be the increased stimulating effects produced by the combination.